2010
DOI: 10.1128/jvi.02598-09
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Variability and Translation Efficiency of the 5′ Untranslated Region of Hepatitis A Virus: Update from Clinical Isolates Associated with Mild and Severe Hepatitis

Abstract: Mutations in the internal ribosome entry site (IRES) of hepatitis A virus (HAV) have been associated with enhanced in vitro replication and viral attenuation in animal models. To address the possible role of IRES variability in clinical presentation, IRES sequences were obtained from HAV isolates associated with benign (n ‫؍‬ 8) or severe (n ‫؍‬ 4) hepatitis. IRES activity was assessed using a bicistronic dual-luciferase expression system in adenocarcinoma (HeLa) and hepatoma (HuH7) cell lines. Activity was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…They suggested that differences in HAV genetic variations of 5 0 non-coding regions 2B and 2C between fulminant and self-limited hepatitis A might cooperatively influence viral replication and virulence. Mackiewicz et al [2010] reported the association of mutations in the internal ribosome entry site of HAV with enhanced in vitro replication, despite lack of relevance to a clinical phenotype. Several studies reported that the viral load might be closely correlated with liver damage and disease severity in mild cases of hepatitis, but not in severe cases [Rezende et al, 2003;Sainokami et al, 2005;Fujiwara et al, 2009].…”
Section: Discussionmentioning
confidence: 96%
“…They suggested that differences in HAV genetic variations of 5 0 non-coding regions 2B and 2C between fulminant and self-limited hepatitis A might cooperatively influence viral replication and virulence. Mackiewicz et al [2010] reported the association of mutations in the internal ribosome entry site of HAV with enhanced in vitro replication, despite lack of relevance to a clinical phenotype. Several studies reported that the viral load might be closely correlated with liver damage and disease severity in mild cases of hepatitis, but not in severe cases [Rezende et al, 2003;Sainokami et al, 2005;Fujiwara et al, 2009].…”
Section: Discussionmentioning
confidence: 96%
“…First, the mutations born in haplotypes ɸ3 (U359C; most frequent), ɸ4 (A513G; negative control), ɸ5 (U590C; alternative IRES structure), ɸ7 (U726C; mutation in pY2), ɸ10 (U590C and U726C) and ɸ16 (U359C, U590C and U726C) were introduced in the G1RL0 bicistronic vector, a modified version of the G1RC21 plasmid, in which the translation of the renilla luciferase gene ( RLuc ) is cap-dependent and that of the firefly luciferase gene ( FLuc ) is dependent on the HAV IRES (Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro assays of IRES activity21 and translation efficiency36 of the VP1 region under study suggested that these minor variants could have higher fitness than the dominant mutants. Additionally, following population dynamics principles, these variants were predicted to be better competitors and colonizers than the major variants, although they were numerically suppressed by them14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these viral factors it may be pointed that some mutations at the 5'NCR of HAV or at the VP1X2A and 2C regions have been associated with fulminant hepatitis (Fujiwara et al, 2002;Fujiwara et al, 2001;Fujiwara et al, 2003) or higher virulence in tamarinds (Emerson et al, 2002), respectively. However, there is no consensus whether the VP1X2A-derived genotypes are clinically different, although some strains belonging to the former genotype VII now included in genotype II were associated with fulminant cases (Ching et al, 2002;Costa-Mattioli et al, 2002;Mackiewicz et al, 2010).…”
Section: Hepatitis a Virus (Hav)mentioning
confidence: 99%